Everyday Offending in Devonport Past and Present Session One: policing Everyday Crime on the Streets - Stevenson, Kim (Law, crime & history, 2023)
This witness seminar was organised by the University of Plymouth in association with the Institute for Contemporary British History, King’s College, London. The event was part of the Annual ESRC Research Festival in 2017 and was hosted by Real Ideas Organisation, Devonport. This transcription was subsequently organised by Culture and Heritage Exchange (CHEx). This session of the Everyday Offending in Devonport Past and Present witness seminar had four panellists (two serving police officers and two retired police officers) and also featured contributions from the audience which was comprised of other serving/ former police officers and local residents.